Indigenous Peoples and Modernization towards Achieving Golden Indonesia - Febrianty, Yenny; Sinaga, Walter A.L.; Brahmana, Rizkita (UNIVERSITAS PAKUAN, 2025)
AbstractThis study aimed to analyze how indigenous law communities in Indonesia adapt to legal modernization in support of the Indonesia Emas 2045 vision. Employing a normative juridical approach supported by empirical data, this research examined the continuity of customary law amidst the transformation of the national legal system, which is increasingly rational, codified, and legalistic. The normative analysis involved a review of relevant legislation and legal doctrines. In contrast, the empirical analysis was drawn from previous case studies that highlighted the interaction between customary law and modernization in various indigenous communities, such as the Baduy, Tolaki, and indigenous communities in Bekasi. The findings revealed that legal modernization has significantly impacted social order, traditional authority, and the cultural values of indigenous law communities. Disruptions are evident in traditional dispute resolution mechanisms, shifts in customary power structures, and transformations from collectivist to more individualistic values. Nevertheless, indigenous law communities exhibit adaptive strategies through the hybridization of customary norms, institutional strengthening via regional regulations, and social movements advocating for the recognition of customary law within the national legal framework. This study recommends the importance of a contextual and inclusive legal approach to ensure that customary law remains vibrant and empowered amidst modernization, serving as an integral component of sustainable legal development toward Indonesia Emas 2045. Keywords: Customary Law, Indigenous Law Communities, Legal Modernization, Social Adaptation, Cultural Identity, National Legal System, Indonesia Emas 2045